Intensification of Recombinant Laccase Production from Sago Bioethanol Liquid Waste and Evaluation of The Enzyme for Synthetic Dye Decolourisation - Nurashikin, Suhaili; Farah Wahida, Mamat; Ngieng, Ngui Sing; Awang Ahmad Sallehin, Awang Husaini; Micky, Vincent; Dayang Salwani, Awang Adeni (Emerald Publishing, 2021)
Purpose: Laccases are polyphenol oxidases that have diverse industrial applications. High industrial demand of laccases has necessitated the development of cost-effective production of recombinant laccases. One of the ways is by utilizing waste stream that has valuable composition for supporting microbial growth and metabolite expression. This work aims to intensify the production of recombinant laccases in Pichia pastoris GS115 using sago bioethanol liquid waste (SBLW) as a feedstock. Method: Production of laccases from SBLW was intensified by the addition of glycerol ranging from 0.5% - 2.5% (w/v). The fermentation performance was assessed based on the biomass concentration and laccase activity. The resulting laccases produced were further evaluated in terms of the capability of the enzyme to decolourise Remazol Brilliant Blue R dye. Results: The results showed that supplementation of SBLW with 2% (w/v) glycerol yielded improvements of 1.9-fold and 2.1-fold of biomass concentration and laccase activity, respectively in comparison to that achieved by fermentations using the standard Buffered Methanol-Complex Medium. Furthermore, the laccases produced using the optimal SBLW medium yielded a decolourisation percentage of 68.6% under non-optimised conditions and in the absence of mediators. The value represents 91% of the decolourising capability of laccases produced using the standard BMMH. Conclusion: In general, this works represents a further step towards low-cost production of recombinant laccases using renewable feedstocks.